Giant recurrent cutaneous squamous cell carcinoma of the gluteal region managed with wide local excision and split-thickness skin grafting in a medically complex patient: a case report - Swarnava Chanda; Abhijith Valsalan; Bellamgari Lakshmi Abhinaya Prudhvi; Dharani Eadelli; Anil Kumar Verma; Abdul Quadir Rahmani (International Surgery Journal, 2026)
Cutaneous squamous cell carcinoma (cSCC) is an invasive malignancy that rarely presents as a giant, exophytic mass in non-sun-exposed regions like the buttocks. We report the case of a 74-year-old male tiles worker with a 15-year history of plaque psoriasis, coronary artery disease (triple vessel disease), hypertension, and type II diabetes mellitus, who presented with a massive recurrent right gluteal cSCC measuring 15×15 cm. The recurrence emerged two years following a primary excision done in 2024. Contrast-enhanced computed tomography (CECT) scan demonstrated extensive superficial infiltration tracking from the L3 to S5 vertebral levels, strictly confined to the skin and subcutaneous layers with completely preserved underlying musculoskeletal planes. Concomitant necrotic bilateral inguinal lymphadenopathy was pathologically confirmed via fine-needle aspiration cytology (FNAC) to be reactive lymphadenitis driven by tumor superinfection rather than metastatic spread. Following optimization of his dual antiplatelet and antidiabetic therapy, the patient underwent an aggressive, margin-negative wide local excision. The massive soft-tissue defect was successfully reconstructed using a meshed split-thickness skin graft (STSG). This case illustrates that giant, locally advanced cSCC can remain anatomically confined to superficial tissue planes, rendering surgical curative resection and immediate autologous skin grafting achievable even in a highly complex cardiovascular patient.